2018
DOI: 10.1021/acsami.8b07081
|View full text |Cite
|
Sign up to set email alerts
|

Easy-to-Use Colorimetric Cyanine Probe for the Detection of Cu2+ in Wilson’s Disease

Abstract: Copper(II) is one of the essential metal elements in human body, which can accumulate in many organs and finally excrete in urine. Excessive load of Cu can cause liver cirrhosis, kidney dysfunction, and many neurological symptoms in the case of Wilson's disease (WD). Therefore, the selective and efficient detection of Cu is of great importance. Although various fluorescent probes have been reported for the detection of Cu, an efficient and capable probe is still rare for patients' self-use on a routine basis. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
34
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(34 citation statements)
references
References 40 publications
0
34
0
Order By: Relevance
“…B UV-Vis-NIR absorption spectra (WD patients' urine/EtOH/HEPES = 10:10:1) of 10 lmol/L CYDA when the pH value was 6.8 (left), 8.0 (right), from top to bottom: CYDA/Urine start , CYDA/Urine end and Urine. Adapted from Shi et al (2018) REVIEW RhoNox to scrutinize Fe 2? release during endocytotic iron uptake (Niwa et al 2018).…”
Section: Fe 2?mentioning
confidence: 99%
“…B UV-Vis-NIR absorption spectra (WD patients' urine/EtOH/HEPES = 10:10:1) of 10 lmol/L CYDA when the pH value was 6.8 (left), 8.0 (right), from top to bottom: CYDA/Urine start , CYDA/Urine end and Urine. Adapted from Shi et al (2018) REVIEW RhoNox to scrutinize Fe 2? release during endocytotic iron uptake (Niwa et al 2018).…”
Section: Fe 2?mentioning
confidence: 99%
“…Also, Cu 2+ catalyzes the creation of reactive oxygen species which can harm basic biological molecules. According to various literatures, the toxicity of Cu 2+ has linked to severe neurological diseases [5], Indian childhood cirrhosis (ICC) and prion diseases [2,4,6,7]. World Health Organization (WHO) has reported that the optimum intake of Cu 2+ for adults SAVRAN et al/Turk J Chem should not go above the level of 10-12 mg.day −1 [8].…”
Section: Introductionmentioning
confidence: 99%
“…Hence, optical probes that could detect Cu 2+ with colorimeter and fluorescence are in great demand since they offer simple, cost-effective methods for rapid and efficient detection of Cu 2+ concentrations. Fluorescent chemosensor, for example, oligo-thiophene-phenylamine based Schiff's bases, 9 ferrocenes based chemosensor, 10 N-benzoyl thioureas, 11 benzimidazole subsidiaries, 12 pyridine acyl thiourea subordinates 13, etc have been accounted for the detection of…”
Section: Introductionmentioning
confidence: 99%